Geopolitics and The Role of The Church in Nationalism on Daily Basis in the 21st Century - Suhartono, Fredric Novando; Novalina, Martina; Samego, Indria; Pasaribu, Andri; Salcido, Sidney (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
Through empirical knowledge, articles, papers, and a daily basis of field observation, this paper proposes an analysis of the current trend on how people usually have pride and a good sense of nationalism towards their nation. An overall analysis and observation of the grand scheme of things on how geopolitics might affect how people could have pride and a good sense of nationalism would be discussed. A thorough and general descriptive discussion on how to light up the nationalism spirit of those who don’t have pride and a good sense of nationalism would be exposed and applied. The application of discussion would be applied through the role of the church in enhancing and inspiring people in nationalism through the right sense of nationalism in both pride and understanding by following the 21st-century trend of behaviour in advanced humanity. Advancing humanity and the right sense of nationalism are the keys to building a better future for a nation.